The Utilization of Ketepeng Cina (Cassia alata L.) Leaves Ethanol Extract as a Prevention of Argulus japonicus Infestation to Gourami Fish (Osphronemus gouramy) - Yudin Ardha Pradipta; Kismiyati Kismiyati; Putri Desi Wulansari (Department of Aquaculture, 2023)
This study aims to determine the benefits and optimal concentration of ketepeng cina leaves (Cassia alata L.) ethanol extract to prevent A. japonicus infestation in gourami fish. This research was conducted in May - August 2019. The research method used is the experimental method. This research design used Complete by Randomized Design (CRD ) with four concentration i.e. Control (P0), 209 ppm (P1), 418 ppm (P2), and 627 ppm (P3). Data was analyzed using Analysis of Variance (Anova) and then followed by Duncan’s Multiple Range Test (DMRT). The results showed that adding ketepeng cina leaves (Cassia alata L.) ethanol extract can prevent Argulus japonicus infestation on gourami fish at the concentration 627 ppm.